Vulvovaginal atrophy: modern approaches to diagnostics and management - Siusiuka, V. H.; Avramenko, N. V.; Pavliuchenko, M. I.; Serhiienko, M. Yu.; Kniazieva, A. O. (Zaporozhye Medical Journal, 2024)
The aim of the review is to analyze the latest data on the current state of diagnosis and management of a common benign vulvar and vaginal disease in postmenopausal women – atrophic vulvovaginitis. The paper presents an analysis of national and foreign scientific publications on the diagnosis and management of vulvovaginal atrophy and also focuses on the modern nomenclature and terminology of this pathology. Vulvovaginal atrophy is a common and progressive condition affecting on average more than 50 % of postmenopausal women, and its development and severity depend mainly on the duration of hypoestrogenism. Such a hormonal imbalance with a gradually increasing estrogen deficiency leads to atrophic changes in the tissues of the female genital organs and thinning of the vaginal epithelium. Degenerative alterations are accompanied by inflammatory phenomena and disturbances in the vaginal microflora. Atrophic lesions in the genitourinary system induce urinary incontinence aggravation, dysuria, increased micturition frequency, and recurrent urinary tract infections. Vulvovaginal atrophy is diagnosed based on appropriate clinical assessments as well as with the involvement of validated questionnaires. Differential diagnosis of the vulvovaginal atrophy should include all pathological conditions imitating the clinical symptoms and signs. Experts of the International Society for the Study of Women’s Sexual Health and the North American Society of Menopause have proposed a new nomenclature, namely, the terms “vulvovaginal atrophy” and “atrophic vaginitis” have been supplanted by “genitourinary menopausal syndrome”. First-line therapy for mild symptoms is non-hormonal vulvar and vaginal lubricants, vaginal moisturizers used on a regular basis. Hormonal therapy (both transdermal and oral) remains the most effective choice for the treatment of clinical manifestations, but contraindications to its use should be considered. In women with contraindications to systemic hormonal therapy, it is possible to prescribe estrogens in the form of vaginal suppositories or vaginal cream. 5-Aminolevulinic acid photodynamic therapy can be one of the promising methods in the treatment of this women’s clinical group. Given the serious consequences of vulvovaginal atrophy for the patients’ health and quality of life, timely diagnosis of the disease in accordance with its specificity and possible complications is of primary importance for the successful treatment and management of this pathology. Conclusions. Vulvovaginal atrophy has been shown to be a common disease, especially among women in the postmenopausal period, based on the analysis of national and foreign scientific publications. The pathogenesis of vulvovaginal atrophy is associated with hypoestrogeny which results in structural and functional abnormalities of the genital organs such as mucus thinning, loss of elasticity, changes in microbiota and increased pH. Given the new nomenclature and terminology, it is appropriate to use the term “genitourinary menopausal syndrome” (GMS or GUMS) in lieu of “vulvovaginal atrophy”.